Association between levels of serum and urinary B cell-activating factor and systemic lupus erythematosus disease activity - Maryam Rezazadeh,; Mohammad Hasan Jokar,; Seyedeh Mehrnaz Aghili,; Zahra Mirfeizi,; Mahmoud Mahmoudi,; Negar Morovatdar,; Kamila Hashemzadeh, (Archives of Rheumatology, 2023)
Objectives: This study investigated the correlation between serum and urinary B cell-activating factor (BAFF) levels and systemic lupus erythematosus (SLE) disease activity. Patients and methods: This case-control study was conducted with 87 participants between December 2020 and September 2021. Sixty-two SLE patients who fulfilled the eligibility criteria were enrolled. SLE patients were categorized into active (n=34) and inactive (n=28) groups based on their Systemic Lupus Erythematosus Disease Activity Index 2000 (SLEDAI-2K) scores. The control group consisted of 25 healthy subjects. Serum and urine samples were collected for the measurement of BAFF levels. Finally, the relationship between these variables and SLE disease activity was investigated. Results: The mean age of active (SLEDAI-2K >4) and inactive (SLEDAI-2K ≤4) SLE patients and healthy individuals were 32.8±7.8, 32.5±6.8, and 31.7±7.8 years, respectively (p=0.62). The median serum BAFF (s-BAFF) and urinary BAFF (u-BAFF) in active lupus patients (10.4 [2.3] ng/mL and 8.2 [3.7] ng/mL, respectively) were significantly higher than in inactive lupus patients (6 (7.1) ng/mL and 1.7 (4.7) ng/mL, respectively; p<0.001) and the control group (3 (3.7) ng/mL and 1.6 (2.2) ng/mL, respectively; p<0.001). However, s-BAFF (p=0.07) and u-BAFF (p=0.43) did not significantly differ between the inactive group and the control group. A significant positive correlation was observed between s-BAFF (r=0.41 and p=0.001) and u-BAFF (r=0.78 and p<0.001) levels and the SLEDAI-2K score. Conclusion: There is a significant positive correlation between serum and urinary BAFF levels and SLE disease activity. Furthermore, significantly higher levels of s-BAFF and u-BAFF have been observed in patients with active lupus compared to inactive and healthy subjects, indicating a possible role for BAFF in the pathogenesis of SLE disease activity.